2002
DOI: 10.1097/00006231-200210000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brain activation caused by caloric stimulation in the case of cochleovestibular denervation - PET study

Abstract: There are a number of well-known stimulation methods for the investigation of the central projection of the vestibular system. In addition to optokinetic, galvanic and neck vibration tests, the most widespread method is caloric stimulation. These listed methods cause not only vestibular, but also other effects on the central nervous system (CNS) (acoustic, tactile and nociceptive). In this paper, positron emission tomography (PET) was used to investigate whether caloric stimulation contains a non-vestibular (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, Danckert and colleagues found increased activation of the ACC when healthy subjects were asked to point while wearing prism glasses, leading to errors between their visual and motor systems (Danckert, Ferber, Goodale 2008). Several other imaging studies using direct vestibular stimulation (caloric and galvanic) and visual stimulation have shown activations of the ACC (Calhoun et al, 2001; Kisely et al, 2002; Miyamoto et al, 2007). We believe the decreased activation of this region after CN-NINM represents the decreased ability of motion in the visual field to induce the sensation of ego-motion and therefore a reduction in the error signal processed by the ACC.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Danckert and colleagues found increased activation of the ACC when healthy subjects were asked to point while wearing prism glasses, leading to errors between their visual and motor systems (Danckert, Ferber, Goodale 2008). Several other imaging studies using direct vestibular stimulation (caloric and galvanic) and visual stimulation have shown activations of the ACC (Calhoun et al, 2001; Kisely et al, 2002; Miyamoto et al, 2007). We believe the decreased activation of this region after CN-NINM represents the decreased ability of motion in the visual field to induce the sensation of ego-motion and therefore a reduction in the error signal processed by the ACC.…”
Section: Discussionmentioning
confidence: 97%
“…As with many phenomena targeted by brain‐imaging studies, the CVS imaging studies are complex however consistent findings of contralateral hemispheric activation have been shown. These activated regions include anterior cingulate cortex (ACC), temporoparietal cortex and insular cortex [detailed below (7–15)]. Such regions have been linked by brain‐imaging, lesion and other studies to the various phenomena affected by CVS.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that there is decreased activity in these areas during the attack compared to the patient's own baseline brain activity. Previous studies have also shown increased activity in these areas during artificial vestibular stimulation as caloric, sound or galvanic stimulation (16)(17)(18).…”
Section: Discussionmentioning
confidence: 89%